Antifouling self-cleaning coating and preparation method thereof

By using UV -curing fluorine -containing clean resin and inorganic silicon resin in the battery case coatings to form a composite coating, solve the problem of easy to absorb the surface of the coating, realize long -term anti -dirt and cleaning effects , Improve the hardness and wear resistance of the coating.

CN119371846AInactive Publication Date: 2025-01-28GUANGDONG XIANGYING CHEM
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411531776.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing UV curing high-gloss coatings are prone to adsorbing pollutants such as dust and oil on the battery shell, causing the surface to become dirty quickly, affecting the beauty, and it is difficult to completely remove pollutants, and the cleaning effect is poor.

Method used

UV curing fluorine -containing easy clean resin and inorganic silicon resin match the modifier to form a composite coating with low surface energy and high -resistant chemicals. Three -dimensional network structures are formed by aggregating and cross -linking reactions to enhance the hardness of the coating The coordination of abrasion resistance and the synergies of nano -carbide, calcium carbonate, and full fluorinel sircles to form a rough structure, which improves the anti -dirt -proof and self -cleaning effect.

Benefits of technology

Achieve long -term anti -dirt and self -cleaning effects, improve the hardness and abrasion resistance of the coating, reduce the adsorption and adhesion of pollutants, extend the life of the coating, and maintain efficient pollution prevention and self -cleaning. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110638460000051
    Figure BDA0005110638460000051
  • Figure BDA0005110638460000061
    Figure BDA0005110638460000061
  • Figure BDA0005110638460000062
    Figure BDA0005110638460000062
Patent Text Reader

Abstract

The invention relates to the field of coatings for battery shells, in particular to an antifouling self-cleaning coating and a preparation method thereof. The invention relates to an antifouling self-cleaning coating which comprises the following components in percentage by mass: 30-40% of UV (Ultraviolet) curing fluorine-containing easy-to-clean resin, 25-30% of UV curing inorganic hybrid silicon resin, 10-15% of lauryl methacrylate, 1-5% of a photoinitiator, 5-10% of a modifier, 1-2% of nano silver oxide, 3-5% of a dispersing agent and a solvent, the modifier is prepared from nano silicon carbide, calcium carbonate whiskers and perfluorooctyltrichlorosilane, and the preparation mass ratio of the nano silicon carbide to the calcium carbonate whiskers to the perfluorooctyltrichlorosilane is 1: (0.5-1): (0.1-0.3). The antifouling and self-cleaning effects of the coating can be effectively improved, the texture similar to the ceramic appearance can be given to the coating, and the broad-spectrum and efficient antibacterial effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings for battery casings, and more specifically, to an antifouling self-cleaning coating and a preparation method thereof. Background Art

[0002] With the advancement of science and technology and the development of industry, the material and surface treatment technology of battery shells are increasingly valued. Battery shells are not only required to have good physical and chemical properties, but also to have excellent appearance and texture to meet the dual needs of modern consumers for product aesthetics and practicality. Imitation ceramic paint, as a high-gloss, high-hardness coating, is highly favored for its ceramic-like texture. This coating is usually cured by high-temperature curing or UV curing, which can significantly improve the appearance quality of the battery shell, making it more beautiful and durable.

[0003] However, although UV-cured high-gloss coatings such as imitation ceramic paints perform well in improving the appearance of battery casings, they also face some problems that cannot be ignored. Due to the smooth surface of the coating, it is easy to absorb pollutants such as dust and oil, causing the surface of the battery casing to quickly become dirty, affecting the appearance. Even with the use of professional cleaning agents, it is difficult to completely remove the pollutants attached to the surface of the coating, and the cleaning effect is not good. This phenomenon seriously affects the use effect of the coating and the overall aesthetics of the battery casing. These problems not only increase the cleaning and maintenance costs of the battery casing, but may also have an adverse effect on the performance of the battery. Summary of the invention

[0004] In order to improve the antifouling and self-cleaning effects of a coating used for a battery casing, the present application provides an antifouling and self-cleaning coating and a preparation method thereof.

[0005] In the first aspect, the present application provides an antifouling self-cleaning coating, which adopts the following technical solution: An antifouling self-cleaning coating comprises the following components by mass percentage: 30-40% UV curing fluorine-containing easy-to-clean resin, 25-30% UV curing inorganic hybrid silicone resin, 10-15% lauryl methacrylate, 1-5% photoinitiator, 5-10% modifier, 1-2% nano silver oxide, 3-5% dispersant, and solvent; The preparation of the modified material includes nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane, and the preparation mass ratio of nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane is 1:(0.5-1):(0.1-0.3).

[0006] During the UV curing process, the active groups in the UV curing fluorine-containing easy-to-clean resin and the UV curing inorganic hybrid silicone resin undergo polymerization and cross-linking reactions under the irradiation of ultraviolet light to form a three-dimensional network structure combined by chemical bonds. This chemical bond is stronger than physical adsorption or weak chemical bond, thereby improving the hardness and wear resistance of the coating.

[0007] The fluorine element in the fluorine-containing resin has low surface energy and high chemical inertness. The cooperation between UV-curing fluorine-containing easy-to-clean resin and UV-curing inorganic hybrid silicone resin produces a synergistic effect. The two penetrate and intertwine with each other during the curing process to form a composite coating with both low surface energy and high chemical resistance. It is not easy to absorb pollutants such as dust and oil, and can effectively resist the erosion of various pollutants, achieving long-term anti-fouling and self-cleaning effects.

[0008] In addition, a modified substance composed of nano silicon carbide, calcium carbonate whisker and perfluorooctyl trichlorosilane is further added to the system of UV-curable fluorine-containing easy-to-clean resin and UV-curable inorganic hybrid silicone resin. With the cooperation of nano silicon carbide, calcium carbonate whisker and perfluorooctyl trichlorosilane, a modified substance with a complex special structure with a rough surface is obtained. The modified substance can be evenly dispersed and suspended in the coating for a long time, is not easy to settle, and gives the coating a good and moderate roughness and hydrophobicity, so that the coating obtained after the coating is dried can maintain a high-efficiency anti-fouling and self-cleaning effect for a long time.

[0009] When nano-silicon carbide and calcium carbonate whiskers work together, they can capture more air to enhance the hydrophobicity of the coating surface; while perfluorooctyltrichlorosilane can give nano-silicon carbide and calcium carbonate whiskers lower surface energy, weakening the adhesion of the coating to droplets, thereby enhancing the anti-fouling and self-cleaning effects.

[0010] Preferably, the preparation mass ratio of the nano-silicon carbide, calcium carbonate whiskers and perfluorooctyltrichlorosilane is 1:0.8:0.2.

[0011] By adopting the above technical solution, the mass ratio of nano-silicon carbide, calcium carbonate whiskers and perfluorooctyltrichlorosilane is further limited, which can help to form a modified product with a special structure, thereby more effectively enhancing the coating effect.

[0012] Preferably, in terms of mass percentage, the UV-curable fluorine-containing easy-to-clean resin is 36%, and the UV-curable inorganic hybrid silicone resin is 27%.

[0013] By adopting the above technical scheme, the dosage relationship of UV-curable fluorine-containing easy-to-clean resin and UV-curable inorganic hybrid silicone resin in the system is further limited, which effectively promotes the formation of a three-dimensional network structure and also provides a good basis for the mixing of other raw materials in the system.

[0014] Preferably, the photoinitiator includes at least one or more of 2959 photoinitiator and TPO photoinitiator.

[0015] Preferably, the photoinitiator is 2959 photoinitiator and TPO photoinitiator, and the mass ratio of 2959 photoinitiator to TPO photoinitiator is 1:(0.25-1).

[0016] Preferably, the solvent includes at least one or more of tetrahydrofuran, acetone, chloroform, dichloromethane and ethyl acetate.

[0017] In a second aspect, the present application provides a method for preparing an antifouling self-cleaning coating, using the following technical solution: A method for preparing an antifouling self-cleaning coating comprises the following steps: Step 1: Preparation of modified substances: Step 1a: Mix and disperse nano-silicon carbide and calcium carbonate whiskers with an organic solvent to obtain a dispersion, wherein the pH value of the organic solvent is adjusted to 4-5; Step 1b: adding perfluorooctyltrichlorosilane to the dispersion, and controlling the temperature at 60-80°C; and continuing the reaction for 3-4 hours after the addition is completed; Step 1c: washing the solution of step 1b, separating and obtaining a solid after the pH is neutral, and obtaining a modified product; Step 2: Mix various raw materials until they are uniform to obtain an antifouling self-cleaning coating.

[0018] By adopting the above technical scheme, a specific method is used to make nano silicon carbide, calcium carbonate whiskers and perfluorooctyltrichlorosilane react with each other to form a modified product with a special structure, which can be stably suspended and evenly dispersed in the coating, thereby more fully playing the role of anti-fouling and self-cleaning.

[0019] After the modified product is prepared, it only needs to be mixed evenly with the other raw materials. The process is simple and suitable for promotion and use in the industry.

[0020] Preferably, in step 1a, the nano-silicon carbide, calcium carbonate whiskers and organic solvent are dispersed under the conditions of ultrasonic power of 1000-1300W and ultrasonic frequency of 15-20KHz.

[0021] By adopting the above technical solution, the ultrasonic dispersion conditions of nano-silicon carbide and calcium carbonate whiskers in organic solvents are further limited, so that nano-silicon carbide and calcium carbonate whiskers can be fully interwoven and mixed, avoiding the situation where a certain substance is too concentrated in a certain place and causes unstable performance.

[0022] Preferably, in the modified material, the organic solvent is an anhydrous ethanol solution, and the solvent for adjusting the pH to 4-5 is glacial acetic acid.

[0023] In summary, this application has the following beneficial effects: 1. This application uses UV-cured fluorine-containing resin with hybrid UV-cured silicone resin as the main body to provide surface scratch resistance and anti-fouling properties, and cooperates with modified substances to achieve self-cleaning. At the same time, nano-carbide can further enhance the strength of the paint film and achieve a texture similar to the appearance of ceramics. With nano-silver particles, it can achieve a broad-spectrum and efficient antibacterial effect without affecting the appearance and performance of the paint film.

[0024] 2. In this application, it is preferred to use a combination of UV-curable fluorine-containing easy-to-clean resin and UV-curable inorganic hybrid silicone resin. During the UV curing process, the active groups of the fluorine-containing resin and the inorganic hybrid silicone resin polymerize and cross-link under ultraviolet light to form a strong three-dimensional network structure, thereby improving the hardness and wear resistance of the coating. The two work together to form a composite coating with low surface energy and high chemical resistance, effectively achieving long-term antifouling and self-cleaning.

[0025] 3. Nano-silicon carbide, calcium carbonate whiskers and perfluorooctyltrichlorosilane work synergistically to form a rough special structured modified product, which is suspended and evenly dispersed in the coating for a long time, enhancing the roughness and hydrophobicity of the coating, increasing air capture on the coating surface, reducing droplet adhesion, improving hydrophobicity, and achieving a long-lasting and efficient anti-fouling self-cleaning effect. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] The raw materials used in the following examples and comparative examples are all commercially available products. Example

[0028] Example 1 An antifouling self-cleaning coating comprises the following components: UV-curing fluorine-containing easy-to-clean resin, UV-curing inorganic hybrid silicone resin, lauryl methacrylate, a photoinitiator, a modifier, nano silver oxide, a dispersant and a solvent.

[0029] The specific amount of each raw material is shown in Table 1.

[0030] The UV curable fluorine-containing easy-to-clean resin is commercially available from Hexin Tiancheng Technology (Tianjin) Co., Ltd., model number UA4500.

[0031] The UV curable inorganic hybrid silicone resin is commercially available from Shuangxin Waterborne Materials (Guangzhou) Co., Ltd., model number W130.

[0032] The photoinitiators are 2959 photoinitiator and TPO photoinitiator.

[0033] The preparation of the modified material includes nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane. During the preparation, the mass ratio of nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane is 1:0.8:0.2.

[0034] The dispersant is commercially available from Guangdong Zhongke Hongtai New Materials Co., Ltd., model K-010.

[0035] The solvent is chloroform.

[0036] The present application also provides a method for preparing an antifouling self-cleaning coating, comprising the following steps: Step 1: Preparation of modified substances: Step 1a: Prepare materials according to the mass ratio of nano-silicon carbide, calcium carbonate whiskers and perfluorooctyltrichlorosilane of 1:0.8:0.2.

[0037] The materials are prepared in a ratio of 1:20 between the total mass of nano-silicon carbide and calcium carbonate whiskers and the mass of the organic solvent.

[0038] The pH of the organic solvent was adjusted to 4-5 with glacial acetic acid.

[0039] Pour nano-silicon carbide and calcium carbonate whiskers into an organic solvent with a pH of 4-5, and perform ultrasonic dispersion under the conditions of an ultrasonic power of 1200 W and an ultrasonic frequency of 18 KHz for 120 minutes to obtain a dispersion.

[0040] Step 1b: The temperature of the dispersion is adjusted to 70° C., and then perfluorooctyltrichlorosilane is added dropwise to the dispersion.

[0041] After the addition was completed, the reaction was continued for 3.5 hours, during which time the mixture was stirred and mixed at 200 r / min.

[0042] Step 1c: The solution of step 1b is repeatedly washed with anhydrous ethanol. After the pH is neutral, a solid is separated and dried and ground to obtain a modified product.

[0043] Step 2: Mix various raw materials until they are uniform to obtain an antifouling self-cleaning coating.

[0044] Example 2 An antifouling self-cleaning coating is different from Example 1 in that the specific content of each raw material is different, see Table 1 for details.

[0045] The mass ratio of nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane is 1:0.5:0.1.

[0046] A method for preparing an antifouling self-cleaning coating is different from that of Example 1 in that some parameters for preparing the modified product are different. Step 1 is specifically as follows: Step 1: Preparation of modified substances: Step 1a: Prepare materials according to the ratio of the total mass of nano-silicon carbide and calcium carbonate whiskers to the mass of organic solvent of 1:20.

[0047] The pH of the organic solvent was adjusted to 4-5 with glacial acetic acid.

[0048] Pour nano-silicon carbide and calcium carbonate whiskers into an organic solvent with a pH of 4-5, and perform ultrasonic dispersion under the conditions of an ultrasonic power of 1000 W and an ultrasonic frequency of 20 KHz for 120 minutes to obtain a dispersion.

[0049] Step 1b: The temperature of the dispersion is adjusted to 60° C., and then perfluorooctyltrichlorosilane is added dropwise to the dispersion.

[0050] After the addition was completed, the reaction was continued for 4 hours, during which time the mixture was stirred and mixed at 200 r / min.

[0051] Step 1c: The solution of step 1b is repeatedly washed with anhydrous ethanol. After the pH is neutral, a solid is separated and dried and ground to obtain a modified product.

[0052] Example 3 An antifouling self-cleaning coating is different from Example 1 in that the specific content of each raw material is different, see Table 1 for details.

[0053] The mass ratio of nano silicon carbide, calcium carbonate whiskers and perfluorooctyltrichlorosilane is 1:1:0.3.

[0054] A method for preparing an antifouling self-cleaning coating is different from that of Example 1 in that some parameters for preparing the modified product are different. Step 1 is specifically as follows: Step 1: Preparation of modified substances: Step 1a: Prepare materials according to the ratio of the total mass of nano-silicon carbide and calcium carbonate whiskers to the mass of organic solvent of 1:20.

[0055] The pH of the organic solvent was adjusted to 4-5 with glacial acetic acid.

[0056] Pour nano-silicon carbide and calcium carbonate whiskers into an organic solvent with a pH value of 4-5, and perform ultrasonic dispersion at an ultrasonic power of 1300 W and an ultrasonic frequency of 15 KHz for 120 minutes to obtain a dispersion.

[0057] Step 1b: The temperature of the dispersion is adjusted to 80° C., and then perfluorooctyltrichlorosilane is added dropwise to the dispersion.

[0058] After the addition was completed, the reaction was continued for 3 hours, during which time the mixture was stirred and mixed at 200 r / min.

[0059] Step 1c: The solution of step 1b is repeatedly washed with anhydrous ethanol. After the pH is neutral, a solid is separated and dried and ground to obtain a modified product.

[0060] Table 1 Example 4 A method for preparing an antifouling self-cleaning coating is different from that of Example 1 in that in step 1a, nano-silicon carbide, calcium carbonate whiskers and an organic solvent are dispersed under an ultrasonic power of 500W.

[0061] Example 5 A method for preparing an antifouling self-cleaning coating is different from that of Example 1 in that in step 1a, nano-silicon carbide, calcium carbonate whiskers and an organic solvent are dispersed under an ultrasonic power of 2500W.

[0062] Comparative Example Comparative Example 1 An antifouling self-cleaning coating, which is different from Example 1 in that nano silicon carbide is replaced by nano aluminum oxide.

[0063] Comparative Example 2 An antifouling self-cleaning coating, which is different from Example 1 in that the calcium carbonate whiskers are replaced by kaolin.

[0064] Comparative Example 3 An antifouling self-cleaning coating, which is different from Example 1 in that perfluorooctyltrichlorosilane is replaced by water.

[0065] Comparative Example 4 An antifouling self-cleaning coating is different from Example 1 in that the UV-curable fluorine-containing easy-to-clean resin is 27 kg and the UV-curable inorganic hybrid silicone resin is 36 kg.

[0066] Performance testing The antifouling self-cleaning coatings of Examples 1-5 and Comparative Examples 1-4 were subjected to contact angle and outdoor rain stain tests with reference to GB / T 31815-2015, and the contact angle, stain resistance (coating reflectance reduction rate) and rain stain grade evaluation are recorded in Table 2.

[0067] Table 2 According to the test data in Table 2, the antifouling self-cleaning coatings of Examples 1-5 all showed no or slight rain stains in the rain stain grade assessment, indicating that the antifouling self-cleaning coatings provided in the present application do have excellent antifouling self-cleaning effects.

[0068] Comparative Examples 1-3 are based on Example 1, and any of the nano silicon carbide, calcium carbonate whisker, and perfluorooctyl trichlorosilane is omitted or replaced. The obtained modified products are applied to the antifouling self-cleaning coating, and the reduction rate of the coating reflection coefficient is much higher than that of Example 1, that is, the antifouling self-cleaning coating of Comparative Examples 1-3 is not as good as that of Example 1 in terms of stain resistance. In the rain stain rating, Comparative Examples 1-3 show obvious or serious rain stains, and are not as good as Example 1 in the rain stain rating. The contact angle of Comparative Examples 1-3 is 98-107°, which is smaller than 128° of Example 1, indicating that Example 1 has better hydrophobicity. In general, the antifouling self-cleaning coating of Example 1 is superior to that of Comparative Examples 1-3 in all aspects. It shows that the special combination of nano silicon carbide, calcium carbonate whisker, and perfluorooctyl trichlorosilane can effectively improve the antifouling and self-cleaning effects of the coating. However, if the special combination of the three is arbitrarily split, a special structure with a rough surface cannot be formed, and the performance of the coating cannot be improved.

[0069] In Examples 4 and 5, based on Example 1, the ultrasonic conditions during the preparation of the modified substance are changed, so that the mixture of nano-silicon carbide and calcium carbonate whiskers cannot reach a predetermined state, thereby affecting the subsequent mixing reaction with perfluorooctyltrichlorosilane, and further affecting the formation of special structures, resulting in a decrease in the performance of the coating. This indicates that not only the combination of nano-silicon carbide, calcium carbonate whiskers, and perfluorooctyltrichlorosilane should be limited, but also the parameters for preparing the modified substance should be further limited in order to give full play to the role of the modified substance.

[0070] Comparative Example 4 is based on Example 1, and destroys the specific dosage matching relationship between the UV-curing fluorine-containing easy-to-clean resin and the UV-curing inorganic hybrid silicone resin in the system. According to the test data in Table 2, the stain resistance and rain stain rating of the coating of Comparative Example 4 in the outdoor rain stain test are significantly reduced, which is obviously not as good as that of Example 1. The contact angle of Comparative Example 4 is also smaller than that of Example 1. It shows that the destruction of the specific dosage matching relationship between the UV-curing fluorine-containing easy-to-clean resin and the UV-curing inorganic hybrid silicone resin in the system has a relatively large impact on the anti-fouling and self-cleaning effects of the coating, and the promoting effect of the basic system on the matching of each raw material is not as good as that of Example 1.

[0071] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An antifouling self-cleaning coating, characterized in that: According to the mass percentage, it includes the following components: 30-40% UV curing fluorine-containing easy-to-clean resin, 25-30% UV curing inorganic hybrid silicone resin, 10-15% lauryl methacrylate, 1-5% photoinitiator, 5-10% modifier, 1-2% nano silver oxide, 3-5% dispersant, and solvent; The preparation of the modified material includes nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane, and the preparation mass ratio of nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane is 1: (0.5-1): (0.1-0.3).

2. The antifouling self-cleaning coating according to claim 1, characterized in that: The preparation mass ratio of the nano silicon carbide, calcium carbonate whisker and perfluorooctyltrichlorosilane is 1:0.8:0.

2.

3. The antifouling self-cleaning coating according to claim 1, characterized in that: According to mass percentage, the UV curing fluorine-containing easy-to-clean resin is 36%, and the UV curing inorganic hybrid silicone resin is 27%.

4. The antifouling self-cleaning coating according to claim 1, characterized in that: The photoinitiator includes at least one or more of 2959 photoinitiator and TPO photoinitiator.

5. The antifouling self-cleaning coating according to claim 4, characterized in that: The photoinitiator is 2959 photoinitiator and TPO photoinitiator, and the mass ratio of 2959 photoinitiator to TPO photoinitiator is 1:(0.25-1).

6. A method for preparing the antifouling self-cleaning coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Preparation of modified substances: Step 1a: Mix and disperse nano-silicon carbide and calcium carbonate whiskers with an organic solvent to obtain a dispersion, wherein the pH value of the organic solvent is adjusted to 4-5; Step 1b: adding perfluorooctyltrichlorosilane to the dispersion, and controlling the temperature at 60-80°C; and continuing the reaction for 3-4 hours after the addition is completed; Step 1c: washing the solution of step 1b, separating and obtaining a solid after the pH is neutral, and obtaining a modified product; Step 2: Mix various raw materials until they are uniform to obtain an antifouling self-cleaning coating.

7. The method for preparing the antifouling self-cleaning coating according to claim 6, characterized in that: In the step 1a, the nano-silicon carbide, calcium carbonate whiskers and organic solvent are dispersed under the conditions of ultrasonic power of 1000-1300W and ultrasonic frequency of 15-20KHz.

8. The method for preparing the antifouling self-cleaning coating according to claim 6, characterized in that: In the modified product, the organic solvent is an anhydrous ethanol solution, and the solvent for adjusting the pH to 4-5 is glacial acetic acid.

Citation Information

Patent Citations

  • UV-curable inorganic-organic hybrid resin and method for preparation thereof

    CA2745075A1

  • Wear-resistant and anti-fouling acrylic modified alkyd coating and preparation method thereof

    CN107793899A

  • Preparation method of modified meerschaum / polyurethane super-hydrophobic / super-oleophobic coating

    CN110922875A

  • Waterproof antifouling photocureable coating as well as preparation method and application thereof

    CN113462232A

  • Anti-aging high-efficiency radiation refrigeration coating and preparation method thereof

    CN114958040A